Contributions to the knowledge of Eylaoidea (Acari: Hydrachnidiae) from China - Li, Hai-Tao; Jin, Dao-Chao; Yi, Tian-Ci; Guo, Jian-Jun (European Journal of Taxonomy, 2022)
This paper enriches the taxonomic study of Eylaoidea Leach, 1816 from China. Eylais (Meteylais) hamata Koenike, 1897 is described to improve the taxonomy of adult Eylaidae Leach, 1816. Meanwhile, a new genus and a new species Pentachares sinensis Li & Guo gen. et sp. nov. is described and illustrated, which belongs to the subfamily Rhyncholimnocharinae Lundblad, 1936 in the family Limnocharidae Grube, 1859. The diagnosis of Rhyncholimnocharinae is modified. Rhyncholimnocharinae is first reported for Chinese fauna. A new key is provided for the subfamilies, genera and subgenera of Limnocharidae.